Factor V Leiden and The Risk of Pulmonary Embolism - Mukesh, Shrestha; Wei, Li (Cardiology and Cardiovascular Medicine, 2019)
Venous thromboembolism (VTE) is the third most common cardiovascular disease which is an under-appreciated contributor to the global burden of non-communicable diseases. Previously pulmonary embolism (PE) and deep vein thrombosis (DVT) were regarded as a single disease entity and still today, public awareness of DVT and PE remains comparatively low. But after recognition of genetic factors, such as Factor V Leiden (FVL), the concept has been changing. More studies are going on to observe the correlation between the genetic factors, such as FVL and PE. Although there is some biasness regarding the concept of factors associated with the PE, the role of possible genetic factors (FVL) remains the main priority in our review.